Omentum adiposity is linked with resistin gene expression - Süsleyici Duman, Belgin; Kaya Dağıstanlı, Fatma; Koldemir-Gündüz, Meliha; Taşkın, Halit Eren; Zengin, Kağan; Kayhan, Figen Esin; Çağatay, Penbe; Taşkın, Mustafa; Öztürk, Melek (My University, 2013)
Background: This study demonstrated site-specific adipose tissue resistin gene expression differences in individuals with and without type 2 diabetes mellitus. The relationship between conventional drug therapy and adipose tissue resistin gene expression was also determined. Paired omental and subcutaneous adipose tissues were excised during elective surgery from morbidly obese and obese patients. Methods: Resistin mRNA expressions were determined by qPCR. All tissue sections also were also analyzed for their resistin and CD68 protein expressions by immunohistochemistry. Results: No significant difference for omental and subcutaneous adipose tissue resistin mRNA expression levels were found among morbidly obese and obese study groups. The omental adipocytes resistin mRNA expressions increased with macrophage number both in the omental and subcutaneus fat. Resistin mRNA expressions of the omental and subcutaneous fat were in positive correlation. As the omental adipocytes radius decreased, the macrophage number increased in subcutaneous fat. In the omentum the adipocytes diameter and areas increased, in correlation with macrophage number. The antidiabetic drug use was found to increase adipocyte size both in the omentum and subcutaneous fat. Conclusions: The higher resistin gene expression in the omental fat may induce the increase in size and number of adipocytes, thus leading to elavation in omental fat mass.
Keywords: Resistin; CD68; Gene expression; Adipose tissue; Drug